The geochemical evidences of sulphur oil sources in the BZ35/36 structures of the Huanghekou Sag, Bohai Bay Basin, China - Qiang Fu; Binbin Liu; Chengmin Niu; Shijie Zhao (Petroleum Research, 2019)
Crude oils in the BZ35/BZ36 fields found within the Paleogene Dongying and Shahejie formations in the Huanghekou Sag of the Bohai Bay Basin, China have generally high density, viscosity, and sulfur content. Their physical properties and geochemical features have obvious differences when compared with crude oils from other structures within the Huanghekou Sag. The comparison and analysis of biomarkers(e.g., pristine/phytane, gammacerane, C24Te/C26TT, C2920S/(20S + 20R), C29ββ/(ββ+αα), etc.) show that sour crude oil from the BZ35/BZ36 fields is similar to the sour oil in the Miaoxi Sag adjacent to the eastern of Huanghekou Sag. Sour, low maturity oils in the Miaoxi Sag have likely migrated southwest, while the sweet, higher maturity oils in the Huanghekou Sag have migrated northeast. Crude oils generated from these two sags have focused in the BZ35/BZ36 structures. The source rock of the sour crude oil was most likely formed in a dry climate and strong reducing saline lake. Keywords: Bohai Bay Basin, Huanghekou sag, Sour crude oil, Biomarker, Hydrocarbon charging